A study on reasons for replacement of hemodialysis tunneled cuffed catheter with polyester sheath and treatment of complications - BAI Ya-fei; CHEN Ru-man; XU Ming-zhi; AN Na; HE Ji-qing; WANG Chun-li; LI Hong (Linchuang shenzangbing zazhi)
Objective To analyze the reasons, complications, treatment methods and treatment results of the replacement of tunneled cuffed catheter(TCC) in the single center in recent six years, and to provide a safe and effective evidence-based basis for TCC replacement. Methods The clinical demographic information of 149 patients with TCC replacement performed in the Blood Purification Center of Hainan Provincial People’s Hospital from April 2013 to April 2019 was collected to make a retrospective analysis on the reasons, complications, treatment Methods and treatment results. Results Among 149 patients with TCC replacement, including 63 males and 86 females, 131 ones had TCC located in right internal jugular vein, and 18 ones in left internal jugular vein. The original puncture point and tunnel were replaced in 129 cases, only the puncture was replaced in 20 cases. TCC was replaced in 71 cases, 30 cases, 25 cases and 19 cases, respectively, because of catheter dysfunction, catheter-related infection, complete/incomplete exfoliation of catheter polyester sheath, and catheter breakage. Conclusions The common causes leading to TCC replacement are: poor catheter function, catheter-related infection, complete/incomplete removal of the catheter polyester sheath, catheter damage. During TCC replacement the following complications may occur: stenosis or occlusion of the central vein, formation of fibrin sheath at the tip of the catheter, catheter incarceration, catheter miscarriage, catheter stump falling into the superior vena cava. Use of some intervention approaches such as fluoroscopy guidance under DSA, angiography and percutaneous catheterization(PTA) may be important means to solve the complications related to TCC replacement.